Outcome of Cerebral Aneurysm Surgery. Hospital Guillermo Almenara Irigoyen, 1983-1996 - Palacios Santos, Fernando (1999)
OBJECTIVE: To identify indicators of outcome following surgery for cerebral aneurysms at Hospital Guillermo Almenara from January 01, 1983 to October 31, 1996. MATERIAL AND METHODS: In a consecutive series of 369 patients who underwent surgery for aneurysms, factors that could affect the outcome, such as age, Hunt and Hess grades, aneurysm location, presence of multiple aneurysms or arterio-venous malformations, and postoperative complications were assessed. RESULTS: 57,7% of patients were female. Mean age was 46,6 ± 14,57 years. 37% of patients were preoperatively classified in Hunt and Hess neurological Grade II, and 34% in Grade III. Single aneurysms were the most frequent (85%). As regards aneurysmal location, intracavernous aneurysms was the most frequent (28,67%). Patient condition at discharge was well in 42,5% of cases and very well in 32,5%. The higher the Hunt and Hess grade, the higher the morbimortality. From those complicated with pneumonia, 50% died. CONCLUSIONS: Postoperative outcome was found to be similar to those of previous reports. Pneumonia constitutes an important postoperative complication.